Nanoparticle-Delivered Multimeric Soluble CD40L DNA Combined with Toll-Like Receptor Agonists as a Treatment for Melanoma - Stone, Geoffrey W. (Public Library of Science, 2009)
Stimulation of CD40 or Toll-Like Receptors (TLR) has potential for tumor immunotherapy. Combinations of CD40 and TLR stimulation can be synergistic, resulting in even stronger dendritic cell (DC) and CD8+ T cell responses. To evaluate such combinations, established B16F10 melanoma tumors were injected every other day X 5 with plasmid DNA encoding a multimeric, soluble form of CD40L (pSP-D-CD40L) either alone or combined with an agonist for TLR1/2 (Pam(3)CSK(4) ), TLR2/6 (FSL-1 and MALP2), TLR3 (polyinosinic-polycytidylic acid, poly(I:C)), TLR4 ( monophosphoryl lipid A, MPL), TLR7 (imiquimod), or TLR9 (Class B CpG phosphorothioate oligodeoxynucleotide, CpG). When used by itself, pSP-D-CD40L slowed tumor growth and prolonged survival, but did not lead to cure. Of the TLR agonists, CpG and poly(I:C) also slowed tumor growth, and the combination of these two TLR agonists was more effective than either agent alone. The triple combination of intratumoral pSP-D-CD40L + CpG + poly(I:C) markedly slowed tumor growth and prolonged survival. This treatment was associated with a reduction in intratumoral CD11c+ dendritic cells and an influx of CD8+ T cells. Since intratumoral injection of plasmid DNA does not lead to efficient transgene expression, pSP-D-CD40L was also tested with cationic polymers that form DNA-containing nanoparticles which lead to enhanced intratumoral gene expression. Intratumoral injections of pSP-D-CD40L-containing nanoparticles formed from polyethylenimine (PEI) or C32 (a novel biodegradable poly(B-amino esters) polymer) in combination with CpG + poly(I:C) had dramatic antitumor effects and frequently cured mice of B16F10 tumors. These data confirm and extend previous reports that CD40 and TLR agonists are synergistic and demonstrate that this combination of immunostimulants can significantly suppress tumor growth in mice. In addition, the enhanced effectiveness of nanoparticle formulations of DNA encoding immunostimulatory molecules such as multimeric, soluble CD40L supports the further study of this technology for tumor immunotherapy.